Antimicrobial efficacy of Еrbium laser in endodontic treatment of infected root canals - Dragidella, Agime (Faculty of Dentistry, Ss. Cyril and Methodius University, Skopje, 2017)
BACKGROUND: This study was conducted to estimate efficacy of Er:YAG laser compared to different antibacterial methods in therapy of infected root canals. Chemo-mechanical irrigation or only instrumentation techniques for cleaning the infected root canals does not ensure complete removal of microorganisms due to anatomy of root dentin, where microorganisms can form complex biofilm or can penetrate into dentin tubules. Repeated infections are possible. Our research determined whether there are differences in disinfecting efficacy between the testing methods, and if laser application with Er:YAG laser could be used in clinical terms as sufficient for therapy. METHODS: In the study 200 freshly extracted premolar single-rooted teeth were included. The crown of each tooth was cut off obtaining 15 mm long root canal. The apical part was drilled through. Teeth were sterilized with absolute alcohol. 200 teeth were equally divided into four groups depending on the strain which were they inoculated with (Enterococcus faecalis, Candida albicans, Streptococcus sanguinis, Fusobacterium nucleatum). The growth of the biofilm was confirmed microbiologically on agar plates. Three different treatments were applied; laser radiation with Er:YAG laser, irrigation with 5.20% NaOCl or Qmix. Viability of microorganisms in the samples after treatments and compared to samples without treatment, were analyzed with a fluorescence method by flow cytometry. RESULTS: Results indicated that all treatment methods effectively eliminated major percent of microbial cells. Statistically significant differences in mean percentage of dead cells between tested organisms (p<0.05) for radiation with Er:YAG laser 30 and 90 seconds, irrigation with 5.20% NaOCl and almost (p=0.052) for irrigation with Qmix were observed. There were statistically significant differences between treatment methods (p<0.001) for all microorganisms, as well as in interaction between tested organisms and treatment methods (p=0.040). The percent of dead cells was significantly higher for C. albicans and S. sanguinis compared to E. faecalis or F. nucleatum in all treatment groups. Longer duration of irradiation showed was statistically significant compared to 30-seconds irradiation (p<0.001) and achieved over 80% of dead cells. Disinfecting activity in combination with irrigant was over 90% for addition of NaOCl and over 95% for addition of Qmix. CONCLUSIONS: According to the results we can conclude that Er:YAG irradiation and its disinfecting capabilities could be used sufficiently as standard disinfection method in endodontics, or can serve as adjuvant therapy to standard mechanical and irrigational treatments. However, this study included only 200 samples, so we need to expand study to more samples of root canals or even in in vivo conditions.
Докторска дисертација одбранета во 2017 година на Стоматолошкиот факултет во Скопје, под менторство на проф. д–р Мира Јанкуловска.